Spotify Wrapped 2023: Pergeseran Perilaku dan Gaya Hidup Gen Z dalam Mengonsumsi Musik - Zorry Stefhan; Farid Rusdi (Prologia, 2026)
The rapid advancement of technology has propelled the popularity of music streaming services, with Spotify emerging as a leader in delivering personalized music-listening experiences. Spotify’s annual Wrapped campaign, which allows users to share their music-listening habits on social media, has become a viral phenomenon, particularly among Gen Z. This study aims to explore Gen Z consumer behavior and the factors driving the success of the 2023 Spotify Wrapped campaign in generating social media virality. Using a qualitative approach with a case study method, the research identified four main factors influencing Gen Z's active participation in sharing Spotify Wrapped: cultural, personal, social, and psychological. The culture of Fear of Missing Out (FoMO) drives engagement with trends, even though not all feel pressured. Personal factors, such as music preferences that reflect self-identity, are a key motivator, with notable recognition of the popularity of music genres like K-pop. Socially, peer influence outweighs celebrity endorsements in sparking curiosity and participation, creating a snowball effect on social media. Psychologically, sharing Spotify Wrapped serves as a way to showcase identity, build connections, and gain social recognition. These findings reveal that the 2023 Spotify Wrapped campaign successfully leveraged these factors to achieve widespread virality among Gen Z. Teknologi yang berkembang telah mendorong popularitas layanan streaming musik. Kampanye tahunan Spotify Wrapped, bahan telah memungkinkan pengguna membagikan kebiasaan mendengarkan musik mereka di media sosial. Hal ini telah menjadi fenomena viral, terutama di kalangan Gen Z. Penelitian ini bertujuan untuk mengeksplorasi perilaku konsumen Gen Z dan faktor-faktor yang mendorong kesuksesan kampanye Spotify Wrapped 2023 dalam menciptakan viralitas di media sosial. Menggunakan pendekatan kualitatif dengan metode studi kasus, penelitian ini menemukan bahwa partisipasi aktif Gen Z dalam membagikan Spotify Wrapped dipengaruhi oleh empat faktor utama: budaya, pribadi, sosial, dan psikologis. Budaya Fear of Missing Out (FoMO) mendorong keterlibatan dengan tren, meskipun tidak semua merasa tertekan. Faktor pribadi, seperti preferensi musik yang mencerminkan identitas diri, menjadi motivasi utama, dengan pengakuan terhadap popularitas genre musik seperti K-pop. Secara sosial, pengaruh teman lebih dominan dibanding selebritas dalam mendorong rasa penasaran dan partisipasi, menciptakan efek bola salju di media sosial. Dari sisi psikologis, berbagi Spotify Wrapped menjadi cara untuk menonjolkan identitas, membangun koneksi, dan memperoleh pengakuan sosial. Temuan ini mengungkap bahwa kampanye Spotify Wrapped 2023 berhasil memanfaatkan faktor-faktor tersebut untuk menciptakan viralitas yang meluas di kalangan Gen Z.